A Phase II Randomized, Double-Blind, Placebo-Controlled Study of the Efficacy, Safety, and Tolerability of Arbaclofen Administered for the Treatment of Social Function in Children and Adolescents With Autism Spectrum Disorders: Study Protocol for AIMS-2-TRIALS-CT1 - Parellada, Mara; San José Cáceres, Antonia; Palmer, Melanie; Delorme, Richard; Jones, Emily J. H.; Parr, Jeremy R.; Anagnostou, Evdokia; Murphy, Declan G. M.; Loth, Eva; Wang, Paul P.; Charman, Tony; Strydom, Andre; et al. (Frontiers in Psychiatry, 2021)
Background: Autism Spectrum Disorder(ASD or autism) is characterized by difficulties in social communication and interaction, which negatively impact on individuals and their families’ quality of life. Currently no pharmacological interventions have been shown to be effective for improving social communication in autism. Previous trials have indicated the potential of arbaclofen for improving social function among autistic children and adolescents with fluent speech. The AIMS2TRIALS Clinical Trial 1 (AIMS-CT1) will examine whether arbaclofen is superior to placebo in improving social function and other secondary outcomes over 16 weeks, along with safety and tolerability profiles. Methods: AIMS CT1 is an international, multi site, double blind, parallel group Phase II randomized clinical trial. It will include 130 males and females aged 5:0 to 17:11 years, with a diagnosis of ASD and fluent speech. Eligible participants will be randomized on a ratio of 1:1 for a 16 week treatment period. Medication will be titrated over five weeks. The primary outcome is the effect on social function from week 0 to week 16 measured on the Socialization domain of the Vineland Adaptive Behavior Scales, 3rd editionTM. Secondary outcome measures include the CGI–S (Clinical Global Impression–Severity), CGI–I (Clinical Global Impression–Improvement), other areas of adaptive function, social communication and other autism symptoms, co occurring behavior problems and health related quality of life. Genetic and electrophysiological markers will be examined as potential stratifiers for treatment response. Exploratory novel digital technologies will also be used to measure change, examining simultaneously the validity of digital biomarkers in natural environments. The safety and tolerability of the drug will also be examined. Our protocol is very closely aligned with a parallel Canadian trial of 90 participants (ARBA Study, US NCT number: NCT03887676) to allow for secondary combined analyses. Outcomes will be compared using both an Intent to Treat and Per Protocol approach. Discussion: The outcomes of this trial, combined with the parallel Canadian trial, will contribute to the evidence base for medications used to help social difficulties among young autistic individuals; demonstrate the capabilities of the AIMS 2 TRIALS network of academic centers to deliver clinical trials; and support future drug development.